Amino acid changes linked to pyrimethamine resistance in the dihydrofolate reductase-thymidylate synthase gene of Plasmodium falciparum. - Cowman, A F (1988)
We describe the isolation and the sequence of the gene for the bifunctional enzyme dihydrofolate reductase-thymidylate synthase (DHFR-TS; EC 1.5.1.3 and EC 2.1.1.45, respectively) from two pyrimethamine-resistant clones of Plasmodium falciparum, HB3 and 7G8. We have also derived the sequence of the DHFR portion of the gene, by amplification using polymerase chain reaction, for the pyrimethamine-sensitive clone 3D7 and the pyrimethamine-resistant strains V-1, K-1, Csl-2, and Palo-alto. The deduced protein sequence of the resistant DHFR portion of the enzyme from HB3 contained a single amino acid difference from the pyrimethamine-sensitive clone 3D7. It is highly likely that this difference is involved in the mechanism of drug resistance in HB3. The sequence of the DHFR gene from other pyrimethamine-resistant strains contains the same amino acid difference from the sensitive clone 3D7. However, they all differ at one other site that may influence pyrimethamine resistance. The DHFR-TS gene is present as a single copy on chromosome 4 in all pyrimethamine-sensitive and pyrimethamine-resistant isolates tested. Therefore, the molecular basis of pyrimethamine resistance in the parasites tested is not amplification of the DHFR-TS gene.